Effect of interest rate changes and dividend announcements on stock returns: Evidence from a frontier economy - Fakhrul Hasan; Umar Nawaz Kayani; Assim Ibrahim Abdel-Razzaq; Tonmoy Choudhury (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
This paper is motivated from previous work in the area of bank interest rate and dividend policy, and we went further to figure out whether there is any association between interest rate changes and the stock market's reaction to dividend announcements. To conduct this research paper, we used 61 Bangladeshi banks out of 66 banks (excluding central bank) from the period from 2010-2021. After using three different types of estimations (OLS, two stage least squared and GMM) we found that when savings interest rate and dividend increase stock market react positively and our result show that stock market react negatively when savings interest rate and dividend decrease. On the other hand, our results show that when loan interest rate and dividend increase stock market react more negatively and if loan interest rate and dividend decrease stock market react more positively.
Keywords: 330; Bangladesh; bank interest rate; savings; loan; dividend; stock market